Investigation of Annealing and Crystallite Size on the Photoluminescence Properties of Ca2Al2SiO7: Eu Phosphors Prepared by Spray Pyrolysis - Fetene Fufa Bakare; Fekadu Gochole Aga; Bona Woliyi Hirpho; Shao-Ju Shih; Wen-Ling Yeh (Advances in Materials Science and Engineering)
Crystalline gehlenite (Ca2Al2SiO7) phosphor, doped with Eu ions, was successfully synthesized by the spray pyrolysis method followed by annealing temperature. The crystallite size and photoluminescence characterization were investigated as function of the annealing temperature. The X-ray diffraction pattern indicates that all peaks could be ascribed to the tetragonal Ca2Al2SiO7 phase in which the dopant could not affect the crystal structures. All annealed powders emitted red luminescence at 613 nm under excitation of 394 nm. However, at 1300°C annealing temperature for Ca2Al2SiO7 doped with Eu ions, the maximum photo luminescent intensity has been obtained.